LEAD EXPOSURE AS A PREMISE FOR LIMITING THE ABILITY TO MAXIMIZE THE REALIZATION OF PHYSICAL ACTIVITY (World Science, 2021)
As a result of man’s technological activities, numerous quantities of lead and its compounds are spread into the environment annually. The long-term effects of low doses of lead on the lungs, heart muscle and the transport function of erythrocytes were investigated.  The study results indicate that long-term intake of small doses of lead, even in the absence of visible clinical manifestations, causes distinct structural changes and therefore, functional changes in the heart muscle, respiratory system, reduces the transport function of erythrocytes, and also possibly limiting the oxygen transport in myocytes and its deposition in tissues and diffusion into cells. There is no doubt that these changes will limit the ability to maximize the realization of physical activity.